Reopening Pandora's Box in Search of a WTO-Compatible Industrial Policy? The Brazil-Taxation Dispute - Emanuel Ornelas; Laura Puccio (Center for Economic Studies and ifo Institute (CESifo), 2019)
The Brazil-Taxation dispute concerns the complaints taken to the World Trade Organisation by the European Union and Japan against seven different Brazilian industrial subsidy programmes. One concerned the automotive sector and represents a clear case of policies dictated by strong domestic political-economy forces, with little attention to impacts on consumers or imports. The ensuing WTO dispute raises important issues concerning the WTO-compatibility of subsidy measures. In particular, the Appellate Body (AB) reversed the panel findings with respect to two issues: the extent to which subsidy measures can be exempted from complying with National Treatment rules under the General Agreement on Tariffs and Trade, and the identification of local content requirements (LCRs), which are prohibited under the Agreement on Subsidies and Countervailing Measures (SCM). In particular, the AB considered that subsidies, if not based on discriminatory taxation, could be justified under the GATT and could have some discriminatory elements without violating the National Treatment disciplines. Furthermore, it concluded that legitimate eligibility criteria under a subsidy programme should not be construed as prohibited LCRs under the SCM. However, the test devised by the AB to distinguish legitimate eligibility criteria from prohibited LCRs could facilitate circumvention of the LCRs prohibition under the SCM.
Keywords: F13; F53; F51; 330; trade policy; dispute settlement; industry subsidies; international trade rules; national treatment; local content requirements